Land Access and Poverty among Agricultural Households in Nigeria - John Chiwuzulum Odozi; Ruth Uwaifo Oyel (Global Labor Organization (GLO), 2024)
The problem of land inequality has attracted renewed interest in the development literature due to its potential effects on the welfare of smallholder farmers. Poverty reduction is an important sustainable development goal and a clearer understanding of the factors that could lead to poverty is important for effective targeted policy initiatives in Nigeria. Investigating the potential relationship between land access and household poverty-related outcomes is of great relevance for both land and social welfare policy and is the focus of our paper. Using data from the four waves of the Nigeria General Household Panel Survey (GHS), we explore how the amount of land an agricultural household operates, and the value of that land, affect the probability of living in poverty. We leverage both a fixed effect and a random correlated effect approach to explore our question of interest. Our results suggest a significant relationship between land access measured by land size and poverty incidence. We also find evidence of nonlinearities in the relationship between land access and poverty.
Keywords: Q15; Q12; D31; I32; I30; O1; 330; Land Access; Land Value; Nigeria; Poverty; Land Size; Inequality